Characterisation of self‐repairing layer formed by oleic acid modified magnesium silicate hydroxide. (10th December 2020) - Qin, Yuan; Wang, Libo; Yang, Gang; Yang, Yi; Wu, Mingxia
Abstract: Serpentine, whose main component is magnesium silicate hydroxide (MSH), has excellent friction properties. To explore the self‐repair mechanism of pure MSH under natural working conditions, MSH was synthesised by hydrothermal method and modified with oleic acid (OA). The optimal concentration of OA‐MSH was added to the air‐conditioning compressor simulator. The self‐repairing layers were studied by scanning electron microscope, Raman, and transmission electron microscope. The results show that OA‐MSH is well uniformly dispersed in lubricating oil and has significant anti‐friction performance. When the concentration is 1.0 wt%, the friction performance is best. The surface self‐repairing layer is composed of a 1.5 μm thick transition layer and a 20 nm amorphous carbon‐based film under the conditions of air‐conditioning compressors. There are dislocation cells, nanocrystals, and Mn2 (Fe 2+, Mg)5 Si8 O22 (OH)2 in the transition layer. The formation mechanism of the self‐repairing layer on piston surface can be divided into three stages: nano‐crystallisation, mechanical alloying and lubricating oil crack deposition.